Interaction Between The Ideal Self, Motivation, Academic Goals and Academic Adaptation Towards The Nurse Graduation of Competency Test - Muhammad Nur; Ririh Yudhastuti; Rika Subarniati; Soernarnatalina Melaniani (Humanistic Network for Science and Technology (HNST), 2018)
Nurse competency test passing rate in Indonesia is still below expectations. There is a correlation between GPA at graduation index. However, there is a similar trend between graduation with underachievement and failure indices with higher GPA. It requires a separate study in addition to the theory and practice of academic ability, need to review internal factors themselves students. This study aimed to analyze the influence of the ideal self, motivation, goal, ability, academic performance and adaptation of learning on nursing graduation of competency test, using a cross sectional design on a number of 119 new graduates of nursing students from two universities in Makassar, Indonesia during July-November 2017. Samples were selected by systematic random sampling. Variable observed were ideal self, academic goals, motivation, learning adaptation, academic ability, and competency test graduation. Bivariate analysis were Pearson correlation and Spearman correlation and the multivariate analysis were Logistic regression and Linear regression. The results showed that the ideal self had a positive correlation with academic goals (rs = 0.240, p = 0.008) and motivation (rs = 0.211, p = 0.021). Multiple linear regression analysis showed that motivation (p = 0.019) and academic purposes (p = 0.000) had a significant influence on learning adaptation. Multiple logistic regression test showed that the learning adaptation (p = 0.037), and the academic ability in theory (p = 0.024) had a significant effect on the graduation of competency test. Graduates nurses must have a corresponding ideal self to improve motivation. Motivation directing and encouraging learning behaviors that affect graduation of competency test. Academic goal setting directs graduates to adapt the learning process. Competence of graduates is not enough with just a written test that predicted by the theory of academic ability, but needs to be equipped with a practice test. Keywords: Ideal self, Academic goals, Learning adaptation, Academic ability in theory and practice, Competency test.